Combinatorial nanomedicines for colon cancer therapy. (10th June 2015) - Anitha, A.; Maya, S.; Sivaram, Amal J.; Mony, U.; Jayakumar, R.
Abstract : Colon cancer is one of the major causes of cancer deaths worldwide. Even after surgical resection and aggressive chemotherapy, 50% of colorectal carcinoma patients develop recurrent disease. Thus, the rationale of developing new therapeutic approaches to improve the current chemotherapeutic regimen would be highly recommended. There are reports on the effectiveness of combination chemotherapy in colon cancer and it has been practiced in clinics for long time. These approaches are associated with toxic side effects. Later, the drug delivery research had shown the potential of nanoencapsulation techniques and active targeting as an effective method to improve the effectiveness of chemotherapy with less toxicity. This current focus article provides a brief analysis of the ongoing research in the colon cancer area using the combinatorial nanomedicines and its outcome. WIREs Nanomed Nanobiotechnol 2015, 8:151–159. doi: 10.1002/wnan.1353 This article is categorized under: Therapeutic Approaches and Drug Discovery > Nanomedicine for Oncologic Disease Nanotechnology Approaches to Biology > Nanoscale Systems in Biology